2020
DOI: 10.1021/acsomega.0c02188
|View full text |Cite
|
Sign up to set email alerts
|

High Regioselectivity Production of 5-Cyanovaleramide from Adiponitrile by a Novel Nitrile Hydratase Derived from Rhodococcus erythropolis CCM2595

Abstract: 5-Cyanovaleramide (5-CVAM) is an important intermediate of a herbicide and chemical raw material. Herein, we found a novel nitrile hydratase from the strain Rhodococcus erythropolis CCM2595, exhibiting high regioselectivity with higher substrate specificity toward dinitriles than mononitriles. In the past, the strain was shown to degrade only phenol, hydroxybenzoate, p -chlorophenol, aniline, and other aromatic compounds. In our study, 20 mM adiponitrile was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In our work, the main product was still 5-cyanovaleramide, though only a small amount of adipamide was produced (Figure 4) when treated with the purified ReNHase only within 2 min. In our previous study, the adiponitrile could completely be consumed within 10 min when it was treated with whole-cell catalysis [16]. The amount of 5cyanovaleramide decreased and the amount of adipamide increased in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In our work, the main product was still 5-cyanovaleramide, though only a small amount of adipamide was produced (Figure 4) when treated with the purified ReNHase only within 2 min. In our previous study, the adiponitrile could completely be consumed within 10 min when it was treated with whole-cell catalysis [16]. The amount of 5cyanovaleramide decreased and the amount of adipamide increased in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 86%
“…Significantly, the purified ReNHase exhibited higher activity during the conversion reaction of different nitriles by shortened catalytic time and increased yield of monocyanate products. In our previous study, during the whole-cell catalysis, 20 mmol L −1 adiponitrile, malononitrile, 2 mmol L −1 terephthalonitrile(after ultrasound, the mixture was homogeneous) could be completely transformed within 10 min, 3 h and 30 min, respectively [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rhodococcus can survive in hostile environments, such as those contaminated with polychlorinated biphenyl [30], nitrophenols, trichloroethene [31], and polycyclic aromatic hydrocarbons [32]. Studies have shown that Rhodococcus can degrade and remove aromatic [33], nitrile [34], sulfuric [35], and nitrogenous compounds [36] in the environment. Indeed, Rhodococcus are commonly used to remediate environmental contamination and pollution [37].…”
Section: Discussionmentioning
confidence: 99%
“…48−50 To combat these issues, protein engineering has been applied to enhance expression, simplify purification, and expand substrate stability and range for various wild NHases. 51,52 Additionally, NHase immobilization is vital for large-scale chemical production, although structural instability and methods like glutaraldehyde cross-linking or MOFs encapsulation may reduce its activity. 53−55 In this study, we introduce a "preblocking" method utilizing VS groups to control NHase immobilization and its surrounding hydrophobic microenvironment.…”
Section: ■ Introductionmentioning
confidence: 99%